Acute One-Cigarette Smoking Decreases Ghrelin Hormone in Saliva: A Pilot Study - Yahia A. Kaabi; Mohiealdeen A. Khalifa (International Journal of Endocrinology)
Cigarette smoking is commonly associated with weight loss and mechanisms for these weight changes are still elusive. Ghrelin is a peptide hormone that works in a neuroendocrine fashion to stimulate hunger and the desire for food intake. Ghrelin is also secreted in saliva, probably to enhance food taste. In the current study, we tested the direct impact of acute cigarette smoking on total ghrelin found in saliva. Methods. Blood and saliva samples were collected from 30 healthy nonsmoker male volunteers before and after one-cigarette smoke. Total ghrelin in serum and saliva was measured by ELISA based method. Results. Data showed a statistically significant reduction in salivary ghrelin after smoking (P<0.0001). In serum, total ghrelin levels were not affected before and after smoking (P=0.1362). Additionally, positive correlation was observed between serum and salivary ghrelin before smoking (r=0.4143 and P=0.0158); however, this correlation was lost after smoking (r=0.1147 and P=0.5461). Conclusion. Acute one-cigarette smoking can negatively affect ghrelin levels in saliva that might contribute to the dull food taste in smokers.